Fibrillogenesis of Tau: Insights from Tau Missense Mutations in FTDP‐17 - Yen, Shu‐Hui (Brain Pathol, 2006)
Frontotemporal dementia and Parkinsonism linked to chromosome 17 (FTDP‐17) is a neurological disorder associated with tau pathology. Tau deposits in FTDP‐17 brains consist of polymerized filaments of hyperphosphorylated tau, the morphology of which is determined by the nature of the tau gene mutation observed in each case. A number of mutations associated with FTDP‐17 have been identified in the 5'splice site of exon 10 and in exons 9–13 of the tau gene. The exon 10 5'splice site mutations disrupt alternative splicing and thus alter the ratio of 4R and 3R Tau isoforms. The majority of Tau missense mutations decrease its ability to bind tubulin and promote microtubule assembly. The extent of reduction varies depending on the site and nature of the mutation. Some Tau missense mutations also have a direct effect on the rate and the extent of tau filament formation. In the presence of polymerization‐inducing agents such as heparin or arachidonic acid, mutant tau forms polymers more efficiently than wild type tau in vitro. Tau mutations affect polymerization at both nucleation and elongation phases. One mutation (R406W) is also known to alter the susceptibility of tau to phosphorylation. Expression of mutant tau in cultured cells changes the cytoskeletal integrity of CHO and COS‐7 cells, but none of the tau transfected cells display tau filament inclusions. These findings suggest involvement of at least two mechanisms in the pathogenesis of FTDP‐17.